ANTIBAKTERI EKSTRAK KAPANG ENDOFIT DARI AKAR KAYU JAWA (Lannea coromandelica (Houtt.) Merr.) - Saiful Bahri; Puteri Amelia; Normala Rachmawati; Aulia Fitri Firdausya; Firdaus Ramadhan (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2021)
Isolation of endophytic fungi from the roots of Lannea coromandelica could be one way to know the presence of antibacterial activity that serves as a traditional medicinal remedy. This study aims to determine the presence of endophytic fungi at the root of L. coromandelica and their extract potential as an antibacterial agent. Endophytic fungi isolation was performed by direct technique and their macroscopic as well as microscopic characteristics were observed. Screening tests were conducted using methanol and ethyl acetate solvents. Antibacterial tests were conducted on Escherichia coli, Bacillus subtilis, and Staphylococcus epidermidis. This study resulted in seven isolates of endophytic fungi (RLC 1A, RLC 1B, RLC 1C, RLC 2, RLC 3, RLC 4, RLC 5) originated from the root of L. coromandelica. RLC 5 isolate exhibited the largest diameter of inhibition activity on the screening tests and the largest diameter on the antibacterial tests. The supernatant extract of RLC 5 isolate showed the highest antibacterial activity against the test bacterium S. epidermidis. Isolasi kapang endofit dari akar Lannea coromandelica dapat menjadi salah satu cara untuk mengetahui adanya aktivitas antibakteri yang berfungsi sebagai obat tradisional. Penelitian ini bertujuan untuk mengetahui keberadaan kapang endofit pada akar L. coromandelica dan potensinya sebagai agen antibakteri. Isolasi kapang endofit dilakukan dengan teknik langsung lalu diamati karakteristik makroskopik dan mikroskopiknya. Uji penapisan dilakukan menggunakan pelarut metanol dan etil asetat. Uji antibakteri dilakukan terhadap Escherichia coli, Bacillus subtilis, dan Staphylococcus epidermidis. Penelitian ini mendapatkan tujuh isolat kapang endofit (RLC 1A, RLC 1B, RLC 1C, RLC 2, RLC 3, RLC 4, RLC 5) yang berasal dari akar L. coromandelica. Isolat RLC 5 memperlihatkan diameter daya hambat terbesar pada uji penapisan dan diameter terbesar pada uji aktivitas antibakteri. Ekstrak supernatan isolat RLC 5 menunjukkan aktivitas antibakteri tertinggi terhadap bakteri uji S. epidermidis.